In suit constructing S-scheme FeOOH/MgIn2S4 heterojunction with boosted interfacial charge separation and redox activity for efficiently eliminating antibiotic pollutant. (July 2022) - Luo, Jin; Lin, Pingping; Zheng, Pilang; Zhou, Xunfu; Ning, Xiaomei; Zhan, Liang; Wu, Zhijun; Liu, Xiangning; Zhou, Xiaosong
Abstract: Photocatalytic elimination of antibiotic pollutant is an appealing avenue in response to the water contamination, but it still suffers from sluggish charge detachment, limited redox capacity as well as poor visible light utilization. Herein, a particular S-scheme FeOOH/MgIn2 S4 heterojunction with wide visible light absorption was triumphantly constructed by in-situ growth of MgIn2 S4 nanoparticles onto the surface of FeOOH nanorods, and employed as a high-efficiency visible light driven photocatalyst for removing tetracycline (TC). Conspicuously, the as-obtained FeOOH(15 wt%)/MgIn2 S4 elucidated the optimal TC removal rate of 0.01258 min −1 after 100 min of visible light illumination, which was almost 33.1 and 6.6 times larger than those of neat FeOOH and MgIn2 S4, separately. The exceptional degradation performance was principally put down to the establishment of S-scheme heterojunction between FeOOH and MgIn2 S4, which could not merely accelerate the detachment of photogenerated carriers, but also retain the powerful reducing ability of photoinduced electrons for MgIn2 S4 and high oxidizing capacity of photoexcited holes for FeOOH, strongly driving the generation of plentiful active species including holes, superoxide and hydroxyl radicals. Additionally, the possible degradation mechanism and pathways of TC were also speculated. This work offers a valuable perspective for constructing high-efficiency S-scheme heterojunction photocatalysts for eradicating antibiotics. Graphical abstract: Image 1 Highlights: A particular S-scheme FeOOH/MgIn2 S4 heterojunction hybrid was constructed. S-scheme FeOOH/MgIn2 S4 heterojunction elucidated the boosted TC removal rate. Enhanced charge transfer was ascribed to the generated S-scheme heterojunction. Possible catalytic mechanism and degradation pathways of TC were speculated.